2020
DOI: 10.1371/journal.pone.0228056
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pneumonia and its associated factors in children from a developing country: A prospective cohort study

Abstract: Introduction Pneumonia in children is a common disease yet determining its aetiology remains elusive. Objectives To determine the a) aetiology, b) factors associated with bacterial pneumonia and c) association between co-infections (bacteria + virus) and severity of disease, in children admitted with severe pneumonia. Methods A prospective cohort study involving children aged 1-month to 5-years admitted with very severe pneumonia, as per the WHO definition, over 2 years. Induced sputum and blood obtained withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 50 publications
2
47
0
10
Order By: Relevance
“…Isolation frequency between 42 and 83% has been documented in numerous health centers in Ethiopia and elsewhere in low-income countries. [22][23][24] Also, a substantial difference in the isolation rate exists between high-and low-income countries, and higher rates from numerous clinical samples were common in countries of the latter category, 25 which is consistent with the data presented in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Isolation frequency between 42 and 83% has been documented in numerous health centers in Ethiopia and elsewhere in low-income countries. [22][23][24] Also, a substantial difference in the isolation rate exists between high-and low-income countries, and higher rates from numerous clinical samples were common in countries of the latter category, 25 which is consistent with the data presented in this study.…”
Section: Discussionsupporting
confidence: 91%
“…While the strict exclusion of risk populations may affect our prevalence rate, the younger age of our patients (less than 6 months) may also be the reason for higher prevalence compared to the previous African studies [ 20 22 ]. Additionally, other viruses and bacteria probably play a more important role in developing countries compared to western settings, where RSV has a much higher importance than other viruses and bacteria [ 2 , 29 , 31 ]. However, vaccination was up to date and almost all infants had a preceding upper respiratory infection in our study, thus bacterial etiologies were unlikely in the majority of the patients, although it was not explored adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing between the severe pneumonia and non-pneumonia groups revealed that CYP with CP along with severe pneumonia were more likely to be male (62% vs. 38%, p < 0.01). According to Nathan’s children prospective cohort study, bacterial pneumonia was seen more in males [ 46 ]. We think some factors play the role in it.…”
Section: Discussionmentioning
confidence: 99%